HEALING ATAU HUSTLING?: STUDI KASUS WORK-LIFE BALANCE MAHASISWA GENERASI Z - Fakhri Arif Billah; Fatimatuzzahro; Khurul Aimmatul Umah (NATUJA: Jurnal Ekonomi Syariah, 2026)
The phenomenon of work-life balance has become an increasingly relevant issue among Generation Z students, particularly those who simultaneously engage in academic and non-academic activities. This study aims to analyze how Generation Z students at Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember interpret the concepts of healing and hustling within their academic lives. The study positions Generation Z as a group facing the dilemma between productivity demands and the need to maintain mental health. This research employed a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation involving active students participating in organizations, side jobs, digital businesses, and other academic activities. The findings reveal that hustling culture encourages students to remain productive and competitive, while healing serves as a coping mechanism for academic and social pressures. The main factors influencing students’ work-life balance include time management, academic pressure, social media exposure, and social support. This study concludes that work-life balance is not merely related to time management, but also to students’ ability to maintain mental health and quality of life amid modern productivity culture.